Spatial ability and learning to program - Jones, Sue; Burnett, Gary (Human Technology, 2008)
Results in introductory computer programming modules are often disappointing, and various individual differences have been found to be relevant. This paper reviews work in this area, with particular reference to the effect of a student’s spatial ability. Data is presented on a cohort of 49 students enrolled on an MSc in Information Technology course at a university in the UK. A measure was taken of their mental rotation ability, and a questionnaire administered that focused on their previous academic experience, and expectations relating to the introductory computer programming module they were studying. The results showed a positive correlation between mental rotation ability and success in the module (r = 0.48). Other factors, such as confidence level, expected success, and programming experience, were also found to be important. These results are discussed in relation to the accessibility of programming to learners with low spatial ability.